Perbandingan Kadar Total Flavonoid Ekstrak Daun Ketapang (Terminalia catappa L) berdasarkan Kekeringan Simplisia dengan Metode Spektrofotometri UV-Vis - Pratiwi, Anastasia Eka; Bulu, Atalia Tamo Ina; Sawal, Rizky Ardian Hartanto; Pitarisa, Agustina Putri (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Traditional treatment remains one of the widely used treatment methods to this day. One of the plants with potential as conventional medicine is the Ketapang leaf (Terminalia catappa L), which belongs to the Combretaceae family. Ketapang leaves contain various compounds such as flavonoids, alkaloids, tannins, and saponins, with flavonoids known for their high antioxidant properties. This study aims to compare the total flavonoid content in fresh and dried Ketapang leaf extracts. The extraction method used is maceration with 96% ethanol solvent. Evaluation includes organoleptic tests, moisture content, drying shrinkage, phytochemical screening, and thin-layer chromatography (TLC). Total flavonoid content testing is conducted using the colorimetric method with UV-Vis spectrophotometry at a wavelength of 430 nm, with quercetin as the standard. The results show that the yield of fresh Ketapang leaves was 8.74% w/w, while dried Ketapang leaves were 8.40% w/w. In the TLC tested, the Rf values of fresh and dried Ketapang leaf extracts were 0.95 and 0.94, respectively. The total flavonoid content in fresh Ketapang leaf extract was 24.19 mgQE/gram, while for dried Ketapang leaf extract it was 16.84 mgQE/gram. Statistical analysis with an independent sample t-test showed a significant difference (p<0.05) between fresh and dried Ketapang leaf extracts.